Food Processing and Packaging Technologies - Recent Advances 2023
DOI: 10.5772/intechopen.108802
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Chapter: Development of Food Packaging Films from Microorganism-Generated Polyhydroxyalkanoates

Abstract: Petroleum-based packaging (PBP) materials cause environmental pollution and toxic substance accumulation because they cannot decompose in nature for a long time. To prevent these problems, a wide variety of food packaging materials emerge as alternatives to PBP. Researchers have already discussed how polysaccharides and biopolymer-based nanocomposites are used in the development of food packaging films. This chapter, we will introduce how the microorganism-generated biopolymer, polyhydroxyalkanoates (PHAs) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 126 publications
0
3
0
Order By: Relevance
“…Awasthi et al and Pereira et al [87,88] reported the production of mcl-PHA using watermelon and apple PHAs are considered an alternative material for conventional plastics due to their similarity to petrochemically derived plastics, better hydrophobicity, relatively high melting point, and optical purity [83]. Current research demonstrates the existence of approximately 150 different PHAs [84], which gained worldwide interest because of their biodegradable, biocompatible, non-toxic, and thermoplastic nature; the polymer characteristics are influenced by the number of carbon atoms present in each HA monomer unit [83].…”
Section: Microbial Biopolymer Packagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Awasthi et al and Pereira et al [87,88] reported the production of mcl-PHA using watermelon and apple PHAs are considered an alternative material for conventional plastics due to their similarity to petrochemically derived plastics, better hydrophobicity, relatively high melting point, and optical purity [83]. Current research demonstrates the existence of approximately 150 different PHAs [84], which gained worldwide interest because of their biodegradable, biocompatible, non-toxic, and thermoplastic nature; the polymer characteristics are influenced by the number of carbon atoms present in each HA monomer unit [83].…”
Section: Microbial Biopolymer Packagingmentioning
confidence: 99%
“…Although PHAs' packaging application seems promising, it has some drawbacks that hamper its industrial production, including restricted functionality, incompatibility with traditional heat treatment processes, sensitivity to thermal degradation, and particularly high manufacturing costs [84,92]. It is therefore necessary to exploit cheap carbon sources such as agricultural waste for PHA production.…”
Section: Microbial Biopolymer Packagingmentioning
confidence: 99%
“…PHAs are biodegradable in the environment due to their biological origin, while still retaining some characteristics of petrochemical plastics. These polymers are predominantly employed in the field of packaging [2,3], with ongoing research exploring their potential applications in the medical field [4] and in agriculture [5]. Figure 1 illustrates the general structure of PHAs.…”
Section: Introductionmentioning
confidence: 99%